Kerukunan dalam Ruang Digital: Representasi Toleransi Beragama dalam Youtube Habib Ja'far Podcast "Class of Religion": Representation of Religious Tolerance in Youtube Habib Ja'far Podcast "Class of Religion" - Ahmad Rizal, Derry; Idamatussilmi, Nilna; Qoulan Ma’rufa, Hana; Bahri, Moh. Syaiful (SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
This study aims to analyze how the Class of Religion podcast, hosted by Habib Ja'far, represents the values of harmony and tolerance between religions in the context of a digital society. This study is motivated by the growing use of new media in religious practices and the need to foster social harmony amid Indonesia's religious pluralism. The method employed is a qualitative approach, utilizing case studies and critical discourse analysis of relevant podcast content. The results of the study show that the Class of Religion not only conveys religious messages but also builds a space for interfaith dialogue through an inclusive, egalitarian, and contextual da'wah narrative. The podcast leverages the power of popular culture and the logic of digital media to convey religious values in a relaxed, humorous, and participatory approach, making it more accessible to young audiences. These findings reflect the process of mediatization of religion, namely the shift in religious practices that are increasingly influenced by the structure and format of the media, as well as the transformation of religious authority into digital public figures. Podcasts are an effective alternative medium in building a new public space that accommodates more open and dialogical religious discourse. This study concludes that the Class of Religion is a real example of how digital da'wah can play a strategic role in strengthening religious harmony in the era of digital communication.